PROFIL MINAT BERWIRAUSAHA MAHASISWA PROGRAM STUDI TATA RIAS AKS-AKK YOGYAKARTA - Tri Warsihapsari (Jurnal Socia Akademika, 2021)
This research aims to find out the entrepreneurship interest of students of The Cosmetology study program at AKS AKK Yogyakarta. After obtaining cosmetology learning, students are expected to have a sense of attraction or entrepreneurship interest in the field. The teaching that has been given both skin beauty and hair beauty can be developed into a business. The study used qualitative descriptive methods involving 20 students in testing the validity of the research data using triangulation methods. Triangulation is by comparing interview data and data obtained from questionnaires. This study stated that the cosmetology learning conducted greatly influenced the entrepreneurship interest of AKS AKK Yogyakarta's cosmetology study program. Learning skin beauty and hair beauty can equip students with skills and knowledge in the field of cosmetology that have the potential to be developed into a business.